The Follistatin‐like Protein 1 Pathway Is Important for Maintaining Healthy Articular Cartilage. Issue 7 (12th June 2020) - Chaly, Yury; Hostager, Bruce; Smith, Sonja; Hirsch, Raphael
Abstract : Objective: We sought to determine whether follistatin‐like protein 1 (FSTL1), a protein produced by articular chondrocytes, promotes healthy articular cartilage and prevents chondrocytes from undergoing terminal differentiation to hypertrophic cells. Methods: In vitro experiments were performed with immortalized human articular chondrocytes. The cells were transduced with a lentivirus encoding human FSTL1 small hairpin RNA or with an adenovirus encoding FSTL1. A quantitative polymerase chain reaction was used for gene expression analysis. Protein expression was assessed by Western blotting. Co‐immunoprecipitation was used to identify interacting partners of FSTL1. FSTL1 expression in human articular cartilage was analyzed using confocal microscopy. Results: Downregulation of FSTL1 expression in transforming growth factor β (TGFβ)‐stimulated chondrocyte pellet cultures led to chondrocyte terminal differentiation characterized by poor production of cartilage extracellular matrix and altered expression of genes and proteins involved in cartilage homeostasis, including MMP13, COL10A1, RUNX2, COL2A1, ACAN, Sox9, and phospho‐Smad3. We also showed that FSTL1 interacts with TGFβ receptor proteins, Alk1 and endoglin, suggesting a potential mechanism for its effects on chondrocytes. Transduction of chondrocytes with an FSTL1 transgene increased COL2A1 expression, whereas it did not affect MMP13 expression. FSTL1 protein expression was decreased in human osteoarthritic cartilage in situ. Conclusion: Our data suggest that FSTL1 plays an important role in maintaining healthy articular cartilage and the FSTL1 pathway may represent a therapeutic target for degenerative diseases of cartilage.